High frequency of complex TP53 mutations in CNS metastases from breast cancer - Lo Nigro, C (Nature Publishing Group, 2012)
BACKGROUND: Brain metastasis from breast cancer is usually associated with a poor prognosis and early death. Alteration of p53 may contribute to malignant progression by abrogation of apoptosis induced by oncogene activation and by acquisition of gain-of-function properties, which promote tumour aggression. Mutation in TP53 occurs at high frequency in carcinomas of the lung and gastro-intestinal tract, but is much less frequent, at 25%, in primary breast cancer. The frequency of TP53 alteration in the central nervous system (CNS) metastatic breast cancer is not known. METHODS: In all, 23 cases of histologically confirmed CNS metastatic breast cancer were identified and the coding sequence of TP53 determined. TP53 was also sequenced in two control series of primary breast carcinomas from independent clinical centres. RESULTS: We demonstrate a strikingly high frequency of TP53 mutation in the CNS metastatic lesions with an over-representation of complex mutations (non-sense/deletions/insertions). Complex mutations occur in metastatic lesions in both triple-negative breast cancer and hormone receptor/HER2-positive cases. Analysis of paired primary carcinomas and brain metastatic lesions revealed evidence for both clonal selection and generation of new mutations (missense and complex) in progression from a primary breast carcinoma to brain metastasis. CONCLUSION: Mutation in TP53 is the most common genetic alteration reported during metastasis to the brain in breast cancer.